Mawlana Mawdudi’s Concept of Political Islam A Critique of Mawlana Wahiduddin Khan - Izzat Raazia; Hassan Shakeel Shah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Syed Abul A'la Mawdudi was a Muslim scholar, ideological thinker, philosopher, jurist and journalist. He worked for the revival of Islam and disseminated his understanding of ‘true Islam’. This paper is categorized into two sections. The first section of this paper aims to explore the concept of Mawlana Mawdudi regarding political Islam and his role as a 20th century Islamic revivalist. The second section deals with critique of Mawlana Wahiduddin Khan on Mawlana Mawdudi’s powerful Islamic ideology. Mawlana Mawdudi viewed Islam as the religion that is all-encompassing and Islamic state as universal that should not be limited to a particular geographical region and Muslims should strive for the establishment of Islamic state through Islamic revolution. In Mawlana Khan’s ‘The Political Interpretation of Islam’, he considered Mawlana Mawdudi’s distinctly political interpretation as problematic.